Dynamics of the N-link pendulum: A fractional perspective - Lopes, António M. (2015)
This paper addresses the dynamics of an N-link planar pendulum in the perspective of fractional calculus. The proposed methodology leads to a novel point of view for signal propagation as a time-space wave within the system mechanical structure. Numerical simulations show the effectiveness of the approach both for signal visualisation and limit cycle detection.